Rotationally Active Ligands: Dialing‐Up the Co‐conformations of a [2]Rotaxane for Metal Ion Binding. (4th September 2016) - Baggi, Giorgio; Loeb, Stephen J.
Abstract: A novel [2]rotaxane was constructed that has a bidentate N, N′‐chelate as part of a rigid, H‐shaped axle and a 24‐membered crown ether macrocycle containing six ether O‐atoms and an olefinic group as the wheel. This unique topology produces a ligand with the ability to dial‐up different donor sets for complexation to metal ions by simply rotating the wheel about the axle. The solution and solid‐state structures of the free ligand and complexes with Li + and Cu + show how the ligand adopts different rotational co‐conformations for each. The Li + ion uses the N, N′‐chelate and O‐donors while the Cu + center is coordinated to both O‐donors and the olefinic group. This concept of rotationally active ligands should be possible with a wide variety of donor sets and could find broad application in areas of coordination chemistry, such as catalysis and metal sequestration.